Embryological Observations of Fruit Development in Mimosa pudica Linn - Shastri, Yogesh C (Plantae Scientia, 2021)
The present paper deals with embryological studies of the fruit development in Mimosa pudica Linn.. Observations on seed coat development is of exotestal pattern and is of multiplicative type, Pericarp is differentiated into epicarp, mesocarp and endocarp were noted.